Acute interstitial nephritis and nephrogenic diabetes insipidus following treatment with sulfamethoxazole‐trimethoprim and temozolomide. Issue 1 (5th October 2020) - Athavale, Akshay; Morris, Jack; Jardine, Meg; Gallagher, Martin; Sen, Shaundeep; Ritchie, Angus; Wang, Amanda Y.
Abstract: We report a case of acute interstitial nephritis with associated nephrogenic diabetes insipidus in a patient treated with temozolomide and sulfamethoxazole‐trimethoprim for glioblastoma multiforme. Kidney biopsy demonstrated focal tubulointerstitial change with tubular dilatation, epithelial change and interstitial inflammation. The patient's kidney function improved with cessation of sulfamethoxazole‐trimethoprim and treatment with hydrochlorothiazide for nephrogenic diabetes insipidus. Recommencement of temozolomide did not result in further deterioration in kidney function. In this case report, we discuss the novel association between sulfamethoxazole‐trimethoprim‐induced acute interstitial nephritis and nephrogenic diabetes insipidus, and suggest possible mechanisms involved. SUMMARY AT A GLANCE: A novel association between the sulfamethoxazole/trimethoprim and acute interstitial nephritis and nephrogenic diabetes insipidus is described in a patient treated with temozolomide for glioblastoma multiforme. Kidney biopsy confirmed acute tubular changes and the patient's kidney function improved with cessation of the drug.